Feeling the burn: the significant burden of febrile nonhemolytic transfusion reactions. Issue 7 (28th March 2017) - Cohen, Robert; Escorcia, Alioska; Tasmin, Farzana; Lima, Ana; Lin, Yulia; Lieberman, Lani; Pendergrast, Jacob; Callum, Jeannie; Cserti‐Gazdewich, Christine
Abstract : BACKGROUND: Febrile nonhemolytic transfusion reactions (FNHTRs) are characterized by a post‐transfusion temperature rise (of ≥ 1°C, to ≥ 38°C) or chills/rigors unrelated to the underlying condition. FNHTRs are provoked by inflammatory cytokines in the product or by host antileukocyte antibodies against residual donor leukocytes. FNHTRs are among the most commonly reported transfusion disturbances and are generally deemed nonserious events. However, their impact on patients and hospitals may be underestimated. STUDY DESIGN AND METHODS: A search through two hemovigilance databases identified all known possible‐to‐definite FNHTRs over 3 years (2013‐2015) at four academic hospitals using prestorage leukoreduced components. FNHTRs were assessed for frequency by product (red blood cells [RBCs], platelets [PLTs], intravenous immunoglobulin), diagnostics (bedside, chest imaging, serology, microbiology), and management (medications, disposition change). The definition of FNHTR was derived from Canada's Transfusion‐Transmitted Injuries Surveillance System. RESULTS: For 437 FNHTRs, the overall per‐product rate across all sites was 0.24%, or 0.17% with RBCs alone and 0.25% with PLTs alone. One‐third of patients had significant fevers (≥ 39.0°C or a rise by ≥ 2.0°C). Approximately one‐quarter underwent chest imaging within 48 hours, and 79% had blood cultures. A hospital admission directly attributable to the FNHTR, to exclude other causes of fever, occurred in 15% of FNHTR outpatients. CONCLUSION: An analysis of FNHTRs reveals a substantial burden of postreaction clinical activity in addition to the disturbance itself. Efforts to avoid this adverse event may save resources, reduce patient distress, and encourage compliance with more restrictive transfusion strategies.